2021
DOI: 10.9734/ajocs/2021/v10i319092
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Additive Effects of Aluminium and Potassium Sulfates in Enhancing the Charge Cycle of Lead Acid Batteries

Abstract: The adoption of aluminium sulfate and potassium sulfate as electrolyte additives were investigated to determine the possibility of enhancing the charge cycle of 2V/ 20AH lead acid battery with reference to the conventional dilute sulfuric acid electrolyte. The duration and efficiency of lead acid batteries have been a challenge for industries over time due to weak electrolyte and insufficient charge cycle leading to sulfation. This has affected the long-term production output in manufacturing companies that de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Chemical reactions that occur when alum (Al2(SO4)3) is inside the lead-acid battery are as follows [6] :…”
Section: Preparation Of Alum Electrolyte Solutionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chemical reactions that occur when alum (Al2(SO4)3) is inside the lead-acid battery are as follows [6] :…”
Section: Preparation Of Alum Electrolyte Solutionmentioning
confidence: 99%
“…According to the findings of Chijioke et al in their study on incorporating alum as a supplement in the electrolyte of PbO2 batteries, the research indicated that there wasn't a notable enhancement in the charge-discharge properties. This lack of improvement stemmed from the limited potential difference between the positive and negative terminals, leading to minimal charge-discharge cycling of the battery [6]. However, according to Zhengyang et al, alum can be used as an additive to PbO2 battery electrolyte because it inhibits sulfation which can enhance battery performance [4].…”
Section: Introductionmentioning
confidence: 99%